Effects of Blue Light on Dynamic Vision - Chen, Hung-Wen; Yeh, Su-Ling (Frontiers in Psychology, 2019)
Dynamic vision is crucial to not only animals’ hunting behaviors but also human activities, and yet little is known about how to enhance it, except for extensive trainings like athletics do. Exposure to blue light has been shown to enhance human alertness (Chellappa et al., 2011), perhaps through intrinsically photosensitive retinal ganglion cells (ipRGCs), which are sensitive to motion perception as revealed by animal studies. However, it remains unknown whether blue light can enhance human dynamic vision, a motion-related ability. We conducted five experiments under blue or orange light to test three important components of dynamic vision: eye pursuit accuracy (EPA, Experiment 1), kinetic visual acuity (KVA, Experiment 1 and 2), and dynamic visual acuity (DVA, Experiment 3-5). EPA was measured by the distance between the position of the fixation and the position of the target when participants tracked a target dot. In the KVA task, participants reported three central target numbers (randomly chosen from 0-9) moving toward participants in the depth plane, with speed threshold calculated by a staircase procedure. In the DVA task, three numbers were presented along the meridian line on the same depth plane, with motion direction (Experiment 3) and difficulty level (Experiment 4) manipulated, and a blue light filter lens was used to test the ipRGCs contribution (Experiment 5). Results showed that blue light enhanced EPA and DVA, but reduced KVA. Further, DVA enhancement was modulated by difficulty level: blue light enhancement effect was found only with hard task in the downward motion in Experiment 3 and with the low contrast target in Experiment 4. However, this blue light enhancement effect was not caused by mechanism of the ipRGCs, at least not in the range we tested. In this first study demonstrating the relationship between different components of dynamic vision and blue light, our findings that DVA can be enhanced under blue light with hard but not easy task indicate that blue light can enhance dynamic visual discrimination when needed.